Treatment of infected Achilles tendinitis and overlying soft tissue defect using an anterolateral thigh free flap in an elderly patient: A case report. Issue 35 (August 2018) - Lee, Young-Keun; Lee, Malrey
Abstract: Introduction: Infected segmental loss of the Achilles tendon with overlying soft tissue and skin defect remains a more complex reconstructive challenge. Here, we present a functional reconstruction of infected Achilles tendinitis with combined soft tissue defects using a free composite anterolateral thigh (ALT) flap with vascularized fascia lata in an elderly patient. Case presentation: A 71-year-old male patient was transferred to our department due to soft tissue defect of the left lower leg and infected Achilles tendinitis. The patient underwent incision and drainage of both lower legs with necrotizing fasciitis in another hospital 2 months ago. Physical examination revealed a 12 × 5 cm wound with exposed Achilles tendon over the posteromedial aspect of lower one-third of the leg. His wound culture grew methicillin-resistant Staphylococcus aureus (MRSA). All infected necrotic Achilles tendon with proximal muscle tissue was excised. The patient underwent successful Achilles tendon reconstruction and soft tissue coverage procedure with a 14 × 7 cm ALT flap with the fascia lata. At the 12-month follow-up, the patient resumed full daily activities, was able to squat, showed a range of motion at the ankle in the 15° dorsiflexion and 45° plantar flexion, and the American Orthopaedic Foot and Ankle Society (AOFAS) score was 94. Conclusion: A free ALT composite flap with the vascularized fascia lata, was successfully used for the treatment of infected Achilles tendinitis with overlying soft tissue defect even in an elderly patient. Furthermore, it provided satisfactory functional and cosmetic outcomes. Hence, the use of free ALT composite flap is highly recommended in such patients.